THE CHARACTERISTICS OF MISDEMEANOR PROSECUTION ACCORDING TO THE LAW ON TAX PROCEDURE AND TAX ADMINISTRATION - Milić, Ivan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
After a misdemeanor and its perpetrator are discovered, the prosecution of the misdemeanor is initiated. Pursuant to the Misdemeanor Law either a request for initiation of a misdemeanor procedure is submitted against the defendant, or a misdemeanor warrant is issued. Without an “initiation act“, a misdemeanor procedure cannot be pursued. In the current Law on Tax Procedure and Tax Administration there are certain specifics concerning the procedure for pursuing defendants of tax misdemeanors. The author focuses on examining the characteristics of this procedure.